Impact of Education on Inappropriate Antibiotic Prescription for Respiratory Tract Infection Based on Physicians' Justifications: A Web-Based Survey in Japan - Ryohei Kudoh; Kosaku Komiya; Norihito Kaku; Yuichiro Shindo; Tatsuya Hayashi; Kei Kasahara; Tomohiro Oishi; Naruhiko Ishiwada; Makoto Ito; Hiroshi Yotsuyanagi; Naoki Hasegawa; Kazuhiro Tateda; et al. (MDPI AG, 2024)
Background: Antibiotics are inappropriately prescribed for respiratory tract infections for various reasons. The differences of the effects of education based on these reasons has not been fully elucidated. This study assessed the impact of an educational film on antibiotic prescription patterns according to physicians' prescribing justifications. Methods: This was a secondary analysis of a nationwide web-based survey involving 1100 physicians. The physicians were required to view a short educational film and determine the need for prescribing antibiotics in simulated scenarios of different acute respiratory tract infectious diseases. The associations between the reasons for antibiotic prescription to patients not requiring antibiotics before viewing the educational film and the positive effects of the intervention were analyzed. Results: The educational intervention positively affected prescribing trends among physicians who prescribed antibiotics for "fever" in mild acute rhinosinusitis (prescription rates from 100% to 25.9%), "pus in the laryngopharynx" in mild acute pharyngitis (prescription rates from 100% to 29.6%), and "purulent sputum" in acute bronchitis without chronic lung disease (prescription rates from 100% to 29.9%) before viewing the film. In contrast, no benefits were observed when the justification was "patient's desire for antibiotics" in mild acute pharyngitis (prescription rates from 100% to 48.5%) and acute bronchitis without chronic lung disease (prescription rates from 100% to 44.0%) or "parents' desire for antibiotics" in narrowly defined common cold in children (prescription rates from 100% to 45.7%). Conclusions: although educational interventions might reduce inappropriate antibiotic prescription by providing accurate knowledge about respiratory tract infections, they appear ineffective for physicians who prescribe antibiotics based on patients' or parents' desires for antibiotic treatment.